The adoption of AI in the South Africa Supply Chain Industry - Naidoo, Prenesen (University of the Witwatersrand, Johannesburg, 2024)
The adoption of Artificial intelligence (AI) in supply chain management shows great promise for the future, by identifying and removing waste, which in turn will increase efficiencies and competitiveness within the supply chain industry. The COVID-19 pandemic has fast tracked the use of technology and AI is no different to other technologies. The significance of the research is to unpack the influence of AI adoption within one of the major industries in South Africa, the study focused on South Africa which has a unique socio-economic landscape. The study unpacks how this influences AI adoption, for example, the skills required to deploy and maintain AI, as well as the potential impact on employment (in a country with a high unemployment rate). The study evaluated the readiness for AI adoption in the country. The study analysed a company that has recently been purchased by an international conglomerate, although the company is a major player in the South African supply chain. The researcher used interviews conducted with executives (senior roles), at a company, as well as existing literature to understand the current adoption of AI in South African supply chains. Thematic analysis of the qualitative data was employed to identify trends in the adoption of AI and understand frameworks that may have been used in the adoption. The research found that there was a case in South Africa for the deployment of AI in the supply chain industry, although South Africa does not have the required socio-economic environment for AI to be deployed, due to the high unemployment, and low readiness for AI adoption, as well as low skills for AI adoption. The implication of the study is understanding the current view of iii where AI adoption falls in the supply chain industry from a priority perspective. Is there an appetite for companies within the Supply Chain industry to adopt AI. The research concludes that a more in-depth study is required extending the research beyond one organisation.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: supply chain; Artificial Intelligence; COVID-19; SDG-9: Industry, innovation and infrastructure